Freedom of speech and hate speech in the democratic state of law - Pereira Silva, Debora; Meneses Cabral, Nuria Micheline; Paixão, Alessandro Gonçalves da (Revista de Direito, 2023)
The article analyzes the relation between Freedom of Speech and Hate Speech, a subject that causes intense debates in the Constitutional Courts. Despite the controversy over the matter, these understandings prevail. The first one defends the supremacy of Freedom of Speech by acting in the presentation and selection of ideas, even if they are not accepted by the society, and improving the democratic debate. In the second understanding, human dignity prevails over freedom of speech, rejecting any discourse of intolerance. Communication would be guided by human dignity inscribed in the constitutional norms. It is noted that the analysis of both fundamental rights obtains multiple interpretations. Therefore, all caution is necessary in the limitation of fundamental rights, because although the legal assets may be in apparent conflict, it is common ground that freedom and dignity are relevant to the democratic-constitutional scenario. O artigo analisa a relação entre Liberdade de Expressão e Discurso de Ódio, tema objeto de intensos debates em Cortes Constitucionais. Apesar da controvérsia sobre a matéria, predominam os seguintes entendimentos. O primeiro defende a supremacia da Liberdade de Expressão atuando na apresentação e seleção de ideias, ainda que estas não sejam aceitas pela coletividade, e fortalecendo o debate democrático. Já no segundo entendimento, a dignidade humana prevalece sobre a liberdade de expressão, rechaçando-se qualquer discurso de intolerância. A comunicação seria balizada pela dignidade humana inscrita nas normas constitucionais. Nota-se que da análise dos dois direitos fundamentais se obtêm múltiplas interpretações. Logo, toda cautela é necessária na limitação de direitos fundamentais, pois embora os bens possam estar em aparente conflito, é pacífico que a liberdade e a dignidade são relevantes para o cenário democrático-constitucional. El artículo analiza la relación entre Libertad de Expresión y Discurso de Odio, tema objeto de intensos debates en Cortes Constitucionales. A pesar de la controversia sobre la materia, predominan los siguientes entendimientos. El primero defiende la supremacía de la Libertad de Expresión actuando en la presentación y selección de ideas, aunque éstas no sean aceptadas por la colectividad, y fortaleciendo el debate democrático. Ya en el segundo entendimiento, la dignidad humana prevalece sobre la libertad de expresión, rechazándose cualquier discurso de intolerancia. La comunicación estaría marcada por la dignidad humana inscrita en las normas constitucionales. Se observa que del análisis de los dos derechos fundamentales se obtienen múltiples interpretaciones. Por lo tanto, toda cautela es necesaria en la limitación de derechos fundamentales, pues aunque los bienes puedan estar en aparente conflicto, es pacífico que la libertad y la dignidad son relevantes para el escenario democrático-constitucional.